2012
DOI: 10.1002/chir.22009
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective copper‐aminopyridine‐catalyzed aza‐Henry reaction with chelating N‐(2‐pyridyl)sulfonyl imines

Abstract: This article describes a copper-catalyzed aza-Henry reaction. Copper complexes of camphor-derived aminopyridines catalyze the addition of nitromethane to N-(2-pyridyl)sulfonyl aldimines to give the corresponding β-nitrosulfonamides with good yields and variable enantiomeric excesses (up to 83%). An example of transformation of these compounds into N-(2-pyridyl)sulfonyl-α-amino acids and deprotection of the sulfonamide with Mg-MeOH is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…13b-14 Among these, the camphor-derived Cu(II)-amino(imino) pyridine complexes have attracted growing attention due to their good-to-high enantioselectivity combined with the advantage of using a cheap ligand available in both enantiomeric forms. [15][16][17][18][19] At rst, we looked at the obtainment of the aldehyde 3 as substrate for the asymmetric Henry reaction (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…13b-14 Among these, the camphor-derived Cu(II)-amino(imino) pyridine complexes have attracted growing attention due to their good-to-high enantioselectivity combined with the advantage of using a cheap ligand available in both enantiomeric forms. [15][16][17][18][19] At rst, we looked at the obtainment of the aldehyde 3 as substrate for the asymmetric Henry reaction (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, the group of Blay and Pedro reported the enantioselective Cu-catalyzed nitro-Mannich reactions of N-(2-pyridyl)sulfonyl imines 117 with nitromethane (Scheme 65). 117 magnesium in MeOH−THF provided a good yield for this transformation.…”
Section: Asymmetric Reactionsmentioning
confidence: 98%
“…In 2012, the group of Blay and Pedro reported the enantioselective Cu-catalyzed nitro-Mannich reactions of N -(2-pyridyl)sulfonyl imines 117 with nitromethane (Scheme ) . They used chiral amino-pyridine ligand 118 in combination with Cu(OTf) 2 and DIPEA to form the β-nitroamine products in moderate to good yields and enantioselectivities.…”
Section: Direct Metal-catalyzed Reactionsmentioning
confidence: 99%
“…A direct approach for the nitro-Mannich reaction, that is, making the nitronate in situ, would be more appealing, yet the only reports of this used an excess of nitro alkane and it was restricted to specically designed imines. [24][25][26][27][28] A turning point occurred in 2019, when Behr et al showed the possibility to use nitrones as imine surrogates, however, the substrate scope was limited to short chain nitro alkanes and required excess base, which in turn limited the functional group tolerability (Scheme 1b). 29 In addition, a large excess of the nitro nucleophile was required, as the authorsobserved that the process was reversible and following formation of the rst nitro-Mannich product, a retro-nitro-Mannich addition occured, redelivering the starting material.…”
Section: Introductionmentioning
confidence: 99%